Trypanosoma cruzi amastigote adhesion to macrophages is facilitated by the mannose receptor (The Rockefeller University Press, 1995)
Trypanosoma cruzi is an obligate intracellular protozoan parasite. The mammalian stage of the parasite life cycle describes amastigotes as an intracellular form that replicates, and trypomastigotes as an extracellular form that disseminates and invades cells. Recent studies, however, have demonstrated that amastigotes circulate in the blood of infected mammals and can invade mammalian cells. In this report, a T. cruzi surface glycoprotein gene, SA85-1.1, was expressed as an immunoglobulin chimera, and this recombinant globulin was used to screen normal mouse tissues for adhesive interactions. This approach identified a subset of macrophages in the skin and peripheral lymph node that bind the T. cruzi surface glycoproteins through the mannose receptor. To further examine the T. cruzi mannose receptor carbohydrate ligands, the interaction between T. cruzi and the mannose-binding protein, a mammalian lectin with similar carbohydrate binding specificities as the mannose receptor, was examined. These studies demonstrated that the mannose-binding protein recognized amastigotes, but not trypomastigotes or epimastigotes, and suggested that amastigotes would also be recognized by the mannose receptor. Therefore, amastigote adhesion to macrophages was investigated, and these experiments demonstrated that the mannose receptor contributes to amastigote adhesion. The data identify the first mammalian lectins that bind to T. cruzi, and are involved in T. cruzi invasion of mammalian cells. The data suggest that amastigotes and trypomastigotes may have developed different mechanisms to adhere to and invade host cells. In addition, it has been established that IFN-gamma-activated macrophages express low levels of the mannose receptor and are trypanocidal; this suggests that the interaction between amastigotes and the mannose receptor enables amastigotes to increase their adherence with a population of macrophages that are nontrypanocidal and permissive for their intracellular replication.